5 Minute Disney - Pixar Stories - Ibrahim, Dalia Mohamed (New York Disney Press, 2012)
Woody and Buzz, Mike and Sulley, Edna and Jack - Jack, plus more - the gang's all here! Get ready to play hide - and - seek under the sea with Dory, climb the Crone's Tooth with Merida and her brothers, fall in love with racing with Lightning McQueen and Cruz Ramirez, and so much more! Each story in this collection is ideal for reading aloud in just five minutes - a perfect fit for bedtome, story time, or any time!
Toy Story 4 : A New Purpose -- Cars 3 : For the love of racing -- The good dinosaur : Arlo's birthday adventure -- Up : Badge building -- Inside out : The riley and bing bong band -- Ratatouille : A Delicious duo -- Monsters university : Teaming up -- Wall.E : Back on Earth -- Coco : The Rivera family band -- Brave : Merida's challenge -- Finding Dory : You're it, Dory! -- Incredibles 2 : Babysitting mode
Available Edition January 2020 at Misr Public Library - Main
Available Edition January 2025 at Misr Public Library - Main
English stories
Keywords: English stories